Canadian Jewish Fertility in Comparative Perspective (2001-2021) - Margolis, Rachel (Canadian Jewish Studies / Études juives canadiennes)

(untitled) (Association for Canadian Jewish Studies / Association d’études juives canadiennes, 2026)
This analysis focuses on two factors leading to changes in Canada’s religious composition—religious differences in fertility and immigration to Canada. I provide updated estimates for Jewish fertility in Canada and its subpopulations, including the first fertility estimates for secular Jews in Canada, those reporting Jewish ethnic origins but no religion. Secular Jews have much lower fertility than those reporting Jewish religion. I then examine how Jewish fertility compares to other religious groups in Canada. Between 2001 and 2021, Jewish fertility remained rather stable, while all other groups experienced considerable decline. Last, I examine how fertility varies within religious groups for those who are born in Canada, those who immigrate to Canada as children, and those who immigrate as adults. I find that for all religions (except those with no religion or “other religions”), the foreign-born who immigrated after age fifteen have, on average, higher fertility than native-born people of the same religion. This work provides important insights into the changing religious landscape in Canada and how Canadian Jews are remaining a stable but small subpopulation in a rapidly changing country.